2021
DOI: 10.1021/acsaem.1c00927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substituting S with Cl on the Structural and Electrochemical Characteristics of Na3SbS4 Solid Electrolytes

Abstract: Herein, we report the synthesis of Na3–x SbS4–x Cl x (0 ≤ x ≤ 0.1) solid electrolytes using a liquid-phase method and describe their structural and electrochemical characteristics. A maximum room-temperature conductivity of 9.0 × 10–4 S cm–1 was achieved in the case of Na2.95SbS3.95Cl0.05 (Cl content = 1.25%). Rietveld analysis based on the X-ray diffraction data indicated that the altered structure due to Cl-substitution involved looser local bonding between Na and S (or Cl) around the Na1 site (Wyckoff 4d p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
1
27
0
3
Order By: Relevance
“…Meanwhile, experiments have demonstrated a room-temperature conductivity maximum by Cl doping, the values are 9.0 × 10 −4 S cm −1 and 2.9 × 10 −3 S cm −1 for x Cl = 0.05 and x Cl = 0.0625, respectively. 60,93,94 These measurements are consistent with the present DFT-MD data for Cl doping, but the experimental doping concentrations are noted to be slightly lower. Although a higher conductivity is exhibited by our prediction, our simulated doping level (at x Cl = 0.125) is apparently difficult to obtain experimentally because of decreased achievable SE pellet density.…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, experiments have demonstrated a room-temperature conductivity maximum by Cl doping, the values are 9.0 × 10 −4 S cm −1 and 2.9 × 10 −3 S cm −1 for x Cl = 0.05 and x Cl = 0.0625, respectively. 60,93,94 These measurements are consistent with the present DFT-MD data for Cl doping, but the experimental doping concentrations are noted to be slightly lower. Although a higher conductivity is exhibited by our prediction, our simulated doping level (at x Cl = 0.125) is apparently difficult to obtain experimentally because of decreased achievable SE pellet density.…”
Section: Resultssupporting
confidence: 87%
“…It is found that using two buffer layers of Na 3 SbS 4 to sandwich the solid electrolyte can greatly improve the EEI stability and the resulting ASSB shows good cycle performance with ah igh capacity maintained around 400 mAh g À1 ,asshown in Figure 3E and F. It should be noted that employing secondary EEI layers with enhanced electrochemical stability,s uch as Na 2.895 W 0.3 Sb 0.7 S 4 ,a re established approaches in ASSB research for enhancing the cycling lifetime. [38,77] Fore xample,i th as been found that hydrating the surface of Na 3 SbS 4 to form Na 3 SbS 4 •9 H 2 Ol eads to electrically insulating decomposition phases,such as NaH and Na 2 O. [78] This is effective in stabilizing the interface by blocking the flow of electrons necessary for further redox decomposition.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…32,46,47,51 In due course of research, the aliovalent doping of Na 3 MX 4 was executed to intentionally introduce such defects. [52][53][54][55][56][57][58][59][60] Among these, the most noteworthy improvement was made via the partial substitution of W 6+ for M 5+ to incorporate Na + vacancies in Na 3 SbS 4 . 56,61 Unprecedentedly high values for σ RT of 30-40 mS cm −1 were reported for Na ∼2.9 W ∼0.1 Sb ∼0.9 S 4 (sintered pellet), which highlighted the importance of defects.…”
Section: Introductionmentioning
confidence: 99%